Book Review Australian Mineral Industry Review for 1970 (The Southern African Institute of Mining and Metallurgy)
Book review AUSTRALIAN MINERAL INDUSTRY REVIEW FOR 1970 The Review is prepared by the Bureau of Mineral Resources, Geology and Geophysics, and gives an interesting and up-to-date account of the Australian minerals industry.